Estimation of in vitro neuroprotective properties and quantification of rutin and fatty acids in buckwheat (Fagopyrum esculentum Moench) cultivated in Turkey - Gulpinar, Ali Rifat; Orhan, Ilkay Erdogan; Kan, Asuman; Senol, Fatma Sezer; Celik, Sadiye Ayse; Kartal, Murat (Elsevier, 2012)
Buckwheat (Fagopyrum esculentum Moench, Polygonaceae) is a popular food crop plant from Polygonaceae. In this study, we investigated the ethyl acetate and ethanol extracts of the seed, stem, and aerial parts of the plant for their neuroprotective effect through acetylcholinesterase, butyrylcholinesterase, and tyrosinase inhibitory and antioxidant activity. Antioxidant activity was measured using the scavenging activity tests against 2,2-diphenyl-1-picrylhydrazyl (DPPH), N,N-dimethyl-p-phenylendiamine (DMPD), superoxide, and hydrogen peroxide radicals and the metal-related methods; metal-chelating capacity and ferric-reducing antioxidant power (FRAP), and phosphomolibdenum-reducing antioxidant power (PRAP) assays. Total phenol and flavonoid contents were calculated spectrophotometrically. Chemical composition of the seed oil was identified by gas chromatography-mass spectrometry (GC-MS) and rutin was quantified by liquid chromatography-mass spectrometry (LC-MS). The extracts were more active against butyrylcholinesterase and highly able to scavenge DPPH. The ethyl acetate extract of the aerial parts and the ethanol extract of the stems displayed a remarkable effect in the FRAP assay. None of the extracts had capacity to chelate the iron. According to LC-MS analysis, the richest plant part in terms of rutin was found to be the aerial parts. GC-MS analysis revealed that the seed oil was dominated by oleic (33.15%), linoleic (31.93%), and palmitic (13.15%) acids. (c) 2011 Elsevier Ltd. All rights reserved.
Keywords: Buckwheat; Fagopyrum esculentum; Cholinesterase inhibition; Antioxidant activity; Rutin; Seed oil; Fatty acids